Listen to Your Heart: Examining Modality Dominance Using Cross-Modal Oddball Tasks - Robinson, Christopher W.; Chadwick, Krysten R.; Parker, Jessica L.; Sinnett, Scott (Frontiers in Psychology, 2020)
The current study used cross-modal oddball tasks to examine cardiac and behavioral responses to changing auditory and visual information. When instructed to press the same button for auditory and visual oddballs, auditory dominance was found with cross-modal presentation slowing down visual response times more than auditory response times (Experiment 1). When instructed to make separate responses to auditory and visual oddballs, visual dominance was found with cross-modal presentation decreasing auditory discrimination and participants also made more visual-based than auditory-based errors on cross-modal trials (Experiment 2). Experiment 3 increased task demands while requiring a single button press and found evidence of auditory dominance, suggesting that it is unlikely that increased task demands can account for the reversal in Experiment 2. Auditory processing speed was the best predictor of auditory dominance, with auditory dominance being stronger in participants who were slower at processing the sounds, whereas, auditory and visual processing speed and baseline heart rate variability did not predict visual dominance. Examination of cardiac responses that were time-locked with stimulus onset showed cross-modal facilitation effects, with auditory and visual discrimination occurring earlier in the course of processing in the cross-modal condition than in the unimodal conditions. The current findings showing that response demand manipulations reversed modality dominance and that time-locked cardiac responses show cross-modal facilitation, not interference, suggest that auditory and visual dominance effects may both be occurring later in the course of processing, not from disrupted encoding.